Exceptional structures > Ordinary materials + Emerging construction technologies - Cruz, Paulo J. S. (2020)
In recent years there has been an increasing number of investigations that expand the way structures are designed and built, by exploring the integration of ordinary building materials – ceramics, concrete, polymers and metal alloys – with emerging construction technologies, namely additive manufacturing processes. This paper presents the most recent activity of the Advanced Ceramics R&D Lab in exploring the use of ceramic and composite materials as contemporary solutions for architectural and structural components.